Arbitrary Power : Romanticism, Language, Politics - Keach, William, 1942- (Book collections on Project MUSE., 2004)
This book explores previously unexamined links between the arbitrary as articulated in linguistic theories on the one hand, and in political discourse about power on the other. In particular, Willam Keach shows how Enlightenment conceptions of the arbitrary were contested and extended in British Romantic writing. In doing so, he offers a new paradigm for understanding the recurrent problem of verbal representation in Romantic writing and the disputes over stylistic performance during this period. With clarity and force, Keach reads these phenomena in relation to a rapidly shifting literary ma.